THE INFLUENCE OF MEDICAL UNDERSTANDING AND PARENTAL VIEWS ON VACCINATIONS REGARDING CHILDREN’S IMMUNIZATION RATES - Bakhromjon M. Mamatqulov; Gulkhayokhon K.Tolipova (Central Asian Journal of Medicine, 2024)
The role of infectious diseases is growing increasingly significant among the primary threats to children’s health, particularly in low- and middle-income countries. Even with advancements in addressing these diseases, child morbidity and mortality remain critical challenges within the healthcare system. Although official statistics indicate a high vaccination rate for children based on the national vaccination calendar, surveys from foreign countries reveal discrepancies between reported vaccination percentages and actual coverage. This highlights the need to obtain an accurate understanding of vaccination rates in our own country.